Urgensi Pengawasan Partisipatif dalam Menciptakan Pilkada 2024 yang Berintegritas di Kabupaten Karawang - Didi Suheri (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2025)
The Regional Head Election (Pilkada) in Indonesia serves as a means of popular sovereignty for electing Governors and Deputy Governors, Regents and Deputy Regents, as well as Mayors and Deputy Mayors. This is a consequence of being a country that adheres to a democratic system. In every election period, Pilkada always faces various challenges, including changing regulations, implementation issues, and oversight mechanisms. One inevitable issue is election violations. The Election Supervisory Agency (Bawaslu) of Karawang, as part of the election organizing body, is responsible for overseeing the implementation of Pilkada in Karawang Regency.One of its programs involves conducting participatory supervision socialization across 30 districts in Karawang Regency. This participatory supervision aims to encourage the public to actively and voluntarily engage in monitoring efforts to ensure an honest and fair Pilkada with integrity.